2021
DOI: 10.3390/nu13061748
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Regulation of Human Brown Adipose Tissue

Abstract: The recent identification of brown adipose tissue in adult humans offers a new strategy to increase energy expenditure to treat obesity and associated metabolic disease. While white adipose tissue (WAT) is primarily for energy storage, brown adipose tissue (BAT) is a thermogenic organ that increases energy expenditure to generate heat. BAT is activated upon cold exposure and improves insulin sensitivity and lipid clearance, highlighting its beneficial role in metabolic health in humans. This review provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 190 publications
0
17
0
Order By: Relevance
“…[41] In line with our results, some authors have suggested that phenolic compounds, which are present in high amounts in EVOO, may be responsible for this browning effect via PGC-1𝛼 activation. [42,43] Nrf2 is a transcription factor that plays a critical role in mitochondrial biogenesis and controls the capacity for adipose tissue expansion. [44] Nrf2 also protects cells against oxidative stress and has a potent anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] In line with our results, some authors have suggested that phenolic compounds, which are present in high amounts in EVOO, may be responsible for this browning effect via PGC-1𝛼 activation. [42,43] Nrf2 is a transcription factor that plays a critical role in mitochondrial biogenesis and controls the capacity for adipose tissue expansion. [44] Nrf2 also protects cells against oxidative stress and has a potent anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] In line with our results, some authors have suggested that phenolic compounds, which are present in high amounts in EVOO, may be responsible for this browning effect via PGC‐1α activation. [ 42 , 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cold acclimation increases the BAT’s oxidative capacity, which correlates with a reduction of shivering thermogenesis [ 94 , 98 ]. Cold adaptation in BAT is also associated with mitochondrial remodeling and vascularization for adaptive thermogenesis [ 91 ] and fatty acid oxidation through UCP1 during high metabolic demands [ 99 ].…”
Section: Cold Exposure and Activation Of Sympathetic Nervous Systemmentioning
confidence: 99%
“…Cold adaptation in BAT is also associated with mitochondrial remodeling and vascularization for adaptive thermogenesis [74] and fatty acid oxidation through UCP1 during high metabolic demands [82].…”
Section: Cold Exposure and Activation Of Sympathetic Nervous Systemmentioning
confidence: 99%